Promoting Creative Skills and Visual Literacy in 5th–7th Grade Students through Art Education - Vosiyeva Aziza To‘xtaqulovna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores methods for promoting creative skills and visual literacy among 5th–7th grade students through art education. Emphasizing project-based learning, collaborative activities, and the use of innovative teaching techniques, the study demonstrates that integrating traditional art practices with modern approaches enhances students’ creativity, critical thinking, and aesthetic understanding. Findings indicate that interactive and experiential teaching strategies significantly contribute to the holistic development of artistic competencies in middle school students.